Paradental cyst: A retrospective study of 10 cases - LIU Xianguang; LI Chenglong; WANG Caijiao; ZHENG Jun; LIU Duanqin; LI Tao (Kouqiang hemian waike zazhi)
[Objective:] To explore the clinical manifestation, imaging features, treatment methods, and prognostic characteristics of paradental cyst (PC), providing reference and basis for clear diagnosis. [Methods:] Retrospective analysis of clinical data of 10 patients with PC treated at the Hospital of Stomatology, Shandong University between September 2016 and September 2022 was performed, including clinical manifestations, imaging features, pathological results, treatment methods and prognosis. [Results:] Among the 10 patients with PC, 8 were male and 2 were female, with an average age of 34.9 years. A total of nine cases occurred in the mandible (five cases involving 48 teeth, four cases involving 38 teeth); one case occurred in the maxilla, involving 18 teeth. Four cases had a partial eruption of affected teeth, while six cases had no eruption of affected teeth. Seven patients presented with symptoms such as swelling and pain, while three had no clinical symptoms. All patients underwent surgical treatment, including curettage of the lesion and extraction of relevant teeth. Follow-up for 1-5 years after surgery showed no recurrence. [Conclusion:] PC is a type of inflammatory root cyst that mainly occurs in the third molar area of the lower jaw. On imaging, it presents a clear crescent-shaped transmission shadow. Swelling and pain are the most common clinical manifestations, and the prognosis of surgical treatment is good.